Running like China : a memoir - Hardcastle, Sophie (Sydney, NSW : Hachette Australia, 2015)
From a talented emerging Australian writer, a brave, honest, unforgettable memoir about mental illness that breaks the silence and shatters the taboos to give hope to all those struggling to find their way through. 'When I was eleven years old Mum told me, "One crowded hour of glorious life is worth an age without a name." Even before I heard these words I was always a child who crammed intense joy into tiny pockets of time.' One day Sophie Hardcastle realised the joy she'd always known had disappeared. She was constantly tired, with no energy, no motivation and no sense of enjoyment for surfing, friends, conversations, movies, parties, family - for anything. Her hours became empty. And then, the month before she turned seventeen, that emptiness filled with an intense, unbearable sadness that made her scream and tear at her skin. Misdiagnosed with chronic fatigue, then major depression, then temporal lobe epilepsy, she was finally told - three years, two suicide attempts and five hospital admissions later - that she had Bipolar 1 Disorder. In this honest and beautifully told memoir, Sophie lays bare her story of mental illness - of a teenage girl using drugs, alcohol and sex in an attempt to fix herself; of her family's anguish and her loss of self. It is a brave and hopeful story of adaptation, learning to accept and of ultimately realising that no matter how deep you have sunk, the surface is always within reach. Running Like China shatters the silence and smashes the taboos around mental illness. It is an unforgettable story.
Title from title screen.
Also available in print.
Also issued in print format.
Mode of access : Available online.
Keywords: Hardcastle, Sophie -- Mental health; Hardcastle, Sophie; Authors, Australian -- Biography; Bipolar disorder in adolescence -- Australia -- Biography; Manic-depressive illness in adolescence -- Australia -- Biography; Manic-depressive illness -- Australia -- Biography; Manic-depressive persons -- Australia -- Biography; People with bipolar disorder -- Australia -- Biography; Australia; Biography & Autobiography - General; Biography & Autobiography - Personal Memoirs; Biography & Autobiography / Social Activists; Biography & non-fiction prose; Biography & True Stories; Children's / Teenage personal & social topics: self-awareness & self-esteem.; Children's / Teenage: Personal & social topics; Children's / Teenage: Social issues; Juvenile Nonfiction - Biography & Autobiography - General; Juvenile Nonfiction - General; Juvenile Nonfiction - People & Places - Australia & Oceania; Juvenile Nonfiction - Social Situations - Emotions & Feelings; Juvenile Nonfiction - Social Situations - General (see Also Headings Under Family); Juvenile Nonfiction - Social Situations - Self-esteem & Self-reliance.; Juvenile Nonfiction / Biography & Autobiography / Social Activists; Juvenile Nonfiction / Biography & Autobiography / Women; Juvenile Nonfiction / Social Topics / Depression & Mental Illness; Memoirs; Personal & social issues: self-awareness & self-esteem (Children's / Teenage); Society & culture: general; Society & social sciences; True stories; True stories: general; Australian; Electronic books; Autobiographies